Factors Associated with Early Acute Kidney Injury in Patients with Acute Decompensated Heart Failure: A Retrospective Observational Study in Bandung, Indonesia - Hawani Sasmaya Prameswari; Fanny Yulia Rachmawati; Rizky Andhika; Indra Wijaya; Januar Wibawa Martha; Lilik Sukesi (Jurnal Kardiologi Indonesia, 2026)
Background: Acute Kidney Injury (AKI) frequently complicates Acute Decompensated Heart Failure (ADHF) and is associated with adverse clinical outcomes. Early recognition of patients at higher risk is clinically important, particularly during the first 48 hours of hospitalization when decongestive treatment and renal monitoring are actively adjusted. Methods: This retrospective observational registry-based study analyzed adult patients hospitalized with ADHF at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, from January 2024 to October 2025. Of 279 screened registry records, 148 were included in the final analysis. AKI was defined as an increase in serum creatinine of at least 0.3 mg/dL within 48 hours after admission. Baseline demographic, clinical, echocardiographic, treatment, and laboratory variables were evaluated using bivariate analysis and multivariable logistic regression. Results: Among 148 included patients, AKI occurred in 67 patients (45.3%). The cohort was predominantly composed of patients with reduced Left Ventricular Ejection Fraction (LVEF), with 145 patients (98.0%) having LVEF <=40%. Admission N-Terminal pro-B-type Natriuretic Peptide (NT-proBNP) >5,000 pg/mL was associated with higher odds of early AKI in the adjusted model (Adjusted Odds Ratio [AOR] 2.04; 95% Confidence Interval [CI] 1.02-4.11; p=0.045). Hypertension and high initial furosemide dose showed nonsignificant trends, whereas other demographic and comorbidity variables did not show statistically significant associations in this cohort. Conclusions: Elevated admission NT-proBNP was associated with early AKI among patients hospitalized with ADHF. However, these findings should be interpreted as exploratory and hypothesis-generating rather than causal or predictive. Validation in larger and more diverse cohorts is required.